Rumen Fermentation and Microbial Protein Synthesis of Bali Cattle Heifers (Bos sondaicus ) Fed Ration Containing Different Energy Protein Level - N. N. Suryani; I. W. Suama; I. G. Mahardika; N.P. Sarini (Universitas Bengkulu, 2020)
The purpose of this study was to determine the effect of energy and protein levels on rumen fermentation, microbial protein synthesis of Bali cattle heifers. The study was conducted in Petang Village, Badung Regency, Province of Bali Indonesia on 12 Bali cattle heifers with initial body weight 193,67 ± 22,55 kg/head. The treatment given is four types of ration consists of different level of metabolizable energy (ME) and crude protein (CP): ME 2051.41 kcal/kg: 12.04% CP (Treatment A); ME 2107.79 kcal/kg : 13.05% CP (Treatment B); ME 2194.06 kcal/kg : 14.04% CP (Treatment C) and ME 2294.23 kcal/kg : 15.09% CP (Treatment D). Variables measured: nutrient intake, rumen fermentation, microbial protein synthesis and growth performance of Bali cattle heifer age of 18 month. This research was a randomized block design. The results showed that increase in ME to 2294.23 kcal /kg and 15.09% CP significantly (P <0.05) increased energy intake to 17,880.57 kcal /day and protein intake 686.56 g /day. Rumen fermentation was also highest (P <0.05) in treatment D seen from total VFA, propionic acid and butyric acid respectively 170.32 mMol, 28.52 mMol and 13.70 mMol. While acetic acid, methane and NGR significantly decreased (P <0.05) respectively 57.77 mMol, 18.38 mMol and 3.07. This resulted in the highest rumen microbial protein synthesis in treatment D which was 562.06 g / day so that it was able to produce the highest ADG too, which was 0.42 kg /day. This study concluded that giving rations containing ME 2294.23 kcal /kg and 15.09% CP increased rumen fermentation and microbial protein synthesis, resulting in the highest growth compared to lower levels.